When Fiction becomes Fact: Effect of Reverse Product Placement on Consumer Attitudes. (3rd May 2016) - Patwardhan, Hemant; Patwardhan, Padmini
ABSTRACT: This exploratory study investigates the persuasive effects of reverse product placement (RPP)—subsequent commercialization of fictional brands from entertainment media into real world products—comparing it with product placement (PP). Persuasion Knowledge Model and Attribution theory were applied to frame hypotheses of effects on brand attitudes along with the constraining effect of skepticism. A mixed test design revealed presence of persuasion knowledge, recognition of persuasive intent, and negative effect of skepticism for PP, but not for RPP. RPP also had a stronger, positive effect on consumer attitudes. Potential application of RPP in new product development and adoption is discussed.